PENGETAHUAN LOKAL MASYARAKAT TANI DALAM MMENGHADAPI PERUBAHAN IKLIM (STUDI KASUS MAYARAKAT TANI DI ACEH BARAT) - Juraida, irma (Jurnal Society : Pengamat Perubahan Sosial, 2025)
AbstractClimate change has become a global and urgent issue, particularly for traditional rice-farming communities that rely on rainfed paddy fields. This study aims to analyze farmers' knowledge and understanding in responding to climate change, with a focus on community-based or local wisdom. This research problem is substantial because farming communities have not yet fully adapted to climate change. Using a qualitative approach with a case study method, this study reveals how farmers interpret natural signs through traditional knowledge, implement sustainable farming practices, and maintain the Keujreun Blang customary institution as a social practice. Additionally, the practice of meuseuraya (mutual cooperation) and the role of customary institutions further strengthen the resilience of traditional farming communities in facing the impacts of climate change. The findings indicate that local knowledge or wisdom is not merely a cultural heritage but also an evolving adaptive practice in response to climate change. Therefore, integrating local knowledge with scientific approaches and government policies is a strategic step in building a more resilient and sustainable agricultural system amidst climate change in the farming communities of West Aceh.